2014
DOI: 10.1002/app.40523
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of end‐functionalized poly(N‐isopropyl acrylamide) with zinc porphyrin and its photocatalytic activity under visible light

Abstract: A series of well‐defined linear poly(N‐isopropyl acrylamide) with an asymmetrical zinc(II) porphyrin (ZnPor–PAM) end group was synthesized by atom transfer radical polymerization, wherein 5,10,15,20‐tetra(p‐bromopropanoyloxyethylphenyl) zinc porphyrin tripropionate was used as the initiator and CuBr/tris(2‐dimeoethyl)amine was used as the catalyst system. The structure of the ZnPor–PAM was characterized by Fourier transform infrared spectroscopy and 1H‐NMR. In addition, the polydispersity index (PDI) obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Porphyrins supported on poly(N-isopropylacrylamide). Duan and co-workers 75,76 developed polymers 17 and 18 (Fig. 7 and Table 3) containing a Zn(II) porphyrin and evaluated their ability as photocatalysts for the oxidative degradation of MB under white light irradiation.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…Porphyrins supported on poly(N-isopropylacrylamide). Duan and co-workers 75,76 developed polymers 17 and 18 (Fig. 7 and Table 3) containing a Zn(II) porphyrin and evaluated their ability as photocatalysts for the oxidative degradation of MB under white light irradiation.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…57 The star-shaped N-and N,N-PAMs were usually synthesized using the arm-first method except for the core first synthesis of the 4-arm s-PNIPAM with the cores of phthalocyanine 35 and porphyrin. 36,37,39 Previously, we reported the core-first synthesis of star-shaped poly(methyl methacrylate)s and poly [2-(dimethylamino)ethyl methacrylate]s with 3-, 4-, 6-, and 12arm by the organocatalytic GTP using the core initiators having corresponding numbers of the SKA group. 59,60 Thus, we aimed to expand the core-first GTP method to the synthesis of the star-shaped N,N-PAM, i.e., s-PDEAM and its double-hydrophilic block acrylamide copolymers, as shown in Scheme 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The combination of ATRP and the click reaction was also utilized for the synthesis of the 7- and 21-arm s-PNIPAMs with the core of β-cyclodextrin, the supramolecular construction of the hyperbranched PNIPAM using the 3-arm s-PNIPAM containing one adamantyl and two β-cyclodextrin moieties at the chain terminals, and the synthesis of the cyclic PNIPAM by the click cyclization of the α-ethynyl,ω-azido-functionalized PNIPAM . In addition, we reported the synthesis of the end-functionalized PINAPMs with cholesterol, monosaccharide, phthalocyanine, porphyrin and the synthesis of the s-PNIPAMs with cores of phthalocyanine and porphyrin based on both the arm-first and core-first approaches. Kakimoto et al reported the preparation of the PNIPAM-grafted silica bead using hyperbranched polysiloxysilane as the polymer brush, which was used for the temperature-responsive HPLC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10−20 For the synthesis of new functional materials, a combination of controlled radical polymerization methods with Pcs is practical and convenient. 21,22 There are three extensively used common controlled radical polymerization techniques, including atom transfer radical polymerization (ATRP), 23,24 reversible addition fragmentation chain transfer polymerization (RAFT), 25 and nitroxide mediated radical polymerization. 26. All of these methods allow us to check the molecular weight and narrow distributions by depressing the number of radical species active during polymerization.…”
Section: Introductionmentioning
confidence: 99%